Implementasi Model Disain Pembelajaran Dick and Carry dalam Mengembangkan Bahan Ajar Materi Bahasa Indonesia Kelas 3 SDN Kemiri 3 - Magdalena, Ina; Apriliani, Aira; Qur’ani, Fathiya Cahaya (TSAQOFAH, 2023)
Quality education is the hope and demand of all education stakeholders. In addition, education is an effort to form a complete human being. Education is also one of the determinants in improving human resources. Teachers as educators play an important role in this matter. One of the efforts that can be made to make it happen is by developing learning designs so as to create effective and efficient learning. The Dick and Carry learning design model is one of the learning models that can be used in developing Indonesian language teaching materials at the elementary school level. This study aims to find out how to develop teaching materials for grade 3 Indonesian materials in elementary schools. Based on empirical results and observations that have been made on the Dick and Carry learning model, it is known that the development of this model is very appropriate to be applied in developing Indonesian language teaching materials, especially at the Grade 3 Elementary School level. This is because the Dick and Carry learning model refers to general stages learning development system, so that this model is appropriately applied in skill-based subjects. In addition to this, the Dick and Carry model has 10 systematic learning steps, from identifying the general learning objectives to carrying out evaluations.